CHEMICAL TRANSFORMATION OF EUGENOL ISOLATED FROM CLOVE OIL TO 4-ALLYL-2-METHOXY-6-SULFONICPHENOL AND 4-ALLYL-2-METHOXY-6-AMINOPHENOL - I Made Sudarma; Maria Ulfa; Sarkono Sarkono (Universitas Gadjah Mada, 2009)
The overall objective of this research was to develop new compounds with potential biological activity from readily accessed natural products, in particular eugenol. Eugenol has been reported to posses antioxidant and anticancer properties. In an attempt to enhance intrinsic activity of this natural compound, some derivatives were possible to synthesize. The main aim of this preliminary research was to isolate eugenol from clove oil and made its sulfonic and amine derivatives through chemical transformation. Clove oil was extracted from clove buds with dichloromethane and followed by isolation of eugenol using column chromatography to afford eugenol (73%). Eugenol has been reported to posses antioxidant and anticancer properties. In an attempt to enhance intrinsic activity of this natural compound, some derivatives were possible to synthesize. Eugenol was transformed to its sulfonic derivative in moderate yield by treatment with chlorosulfonic acid and to its amine by reduction of its nitro derivative. This transformation was rapidly confirmed by GC-MS analysis which showed significance molecular ion at m/z 244 corresponding to molecular formula C10H12SO5. and at m/z 179 corresponding to molecular formula C10H11O2NH2.